MEDIATION ACTS FROM EMPLOYEE ENGAGEMENT WHICH AFFECTS THE EMPLOYEE COMPETENCIES AND INNOVATIVE WORK BEHAVIOUR ON EMPLOYEE PERFORMANCE AT PT TETRA PAK INDONESIA - Budiprasetia, Andika; Johanes Lo, Singmin (Dinasti Publisher, 2021)
These research was intend to discovered the mediate acts from employee engagement in influencing the affect of employee competence and innovative behaviour on Employees' performance at PT Tetra Pak Indonesia. These research population here used saturated sample from all service engineer employees, with a total sample of 76 service engineers. The data analysis method used Structural Equation Model-Partial Least Square (SEM PLS). The research outcomes showed that innovative behaviour did not have an significant affect towards Employee performance. Competence had an positive impact in increasing the employee engagement and also this employee engagement could be able to motivate the Innovative behaviour and Employee performance